Wedding planner system - Sarah Damia, Ahmad Shukri (2019)
Wedding planners are given the responsibility of guiding couples with ideas for their wedding. One of the issues that the wedding planner needs to consider and develop is to manage their time without always to see the wedding planner. This system will make the user save their own time. This project describes in detail the model of the events. Scheduling theory and project management techniques suitable for providing an order of events on a wedding day are then discussed in the context of this project. One of these techniques is then implemented and evaluated using real life data.